Phenotypic Heterogeneity of Monogenic Frontotemporal Dementia - Benussi, Alberto; Padovani, Alessandro; Borroni, Barbara (Frontiers in Aging Neuroscience, 2015)
Frontotemporal dementia (FTD) is a genetically and pathologically heterogeneous disorder characterized by personality changes, language impairment and deficits of executive functions associated with frontal and temporal lobe degeneration. Different phenotypes have been defined on the basis of presenting clinical symptoms, i.e. the behavioral variant of FTD (bvFTD), the agrammatic variant of Primary Progressive Aphasia (avPPA) and the semantic variant of PPA (svPPA). Some patients have an associated movement disorder, either parkinsonism, as in Progressive Supranuclear Palsy (PSP) and Corticobasal Syndrome (CBS), or motor neuron disease (FTD-MND). A family history of dementia is found in 40% of cases of FTD and about 10% have a clear autosomal dominant inheritance. Genetic studies have identified several genes associated to monogenic FTD: microtubule-associated protein tau (MAPT), progranulin (GRN), TAR DNA-binding protein 43 (TARBDP), valosin-containing protein (VCP), charged multivesicular body protein 2B (CHMP2B), fused in sarcoma (FUS) and the hexanucleotide repeat expansion in intron 1 of the chromosome 9 open reading frame 72 (C9orf72). Patients often present with an extensive phenotypic variability, even among different members of the same kindred carrying an identical disease mutation. The objective of the present work is to review and evaluate available literature data in order to highlight recent advances in clinical, biological and neuroimaging features of monogenic frontotemporal lobar degeneration and try to identify different mechanisms underlying the extreme phenotypic heterogeneity that characterizes this disease.